Macroglobulinemia de Waldenström: primer caso con confirmación molecular en Honduras (Revista Médica Hondureña, 2022)
Flora Duarte https://orcid.org/0000-0002-9707-9864Rafael Mojica https://orcid.org/0000-0003-2582-8851Eda Sofía Cálix https://orcid.org/0000-0001-8700-8803Carlos José Fajardo https://orcid.org/0000-0002-6850-8308Abigail Artica https://orcid.org/0000-0001-7951-3703Danilo Alvarado https://orcid.org/0000-0002-1362-2920